Maqashid Sharia Approaches in Pension Fund Programs: Bank Muamalat Indonesia and Taspen Comparison - M. Iqbal; Pamuji; Ajeng Permata Sari; Fernandho; Paul Atagamen Aidonojie (Asy-Syari'ah, 2025)
Pension funds function as instruments for long-term welfare protection; however, their development in Indonesia remains constrained by low financial literacy, limited public participation, and governance and fiscal sustainability issues, including investment irregularities in state pension institutions. In line with rising demand for sharia-compliant financial instruments, the Maqashid Sharia framework emphasizes welfare (maslahah), accountability, and risk mitigation. This study aims to analyze the implementation of pension fund programs at Bank Muamalat Indonesia and Taspen through a Maqashid Sharia lens, by examining governance structures, investment mechanisms, and the alignment of programs with welfare objectives and system sustainability. This qualitative case study relies on secondary data, including corporate profiles, portfolios, participant statistics, and financial reports of Taspen and DPLK Syariah Muamalat. The findings indicate that Taspen’s defined benefit, pay-as-you-go scheme provides benefit certainty for civil servants and their heirs, thereby fulfilling individual-level maslahah (hifz al-nafs, hifz al-nasl). However, from a macro-Maqashid perspective, it imposes a heavy fiscal burden on the state budget, undermines hifz al-mal at the state level, and exposes the state to governance and investment risks. Conversely, DPLK Syariah Muamalat program, grounded in sharia principles, supervised by a Sharia Supervisory Board, and operated under a defined contribution scheme with selectable investment packages, is more closely aligned with Maqashid Sharia (hifz al-din, al-mal, al-nafs, al-nasl, al-‘aql), although its outreach remains limited. The study recommends gradual reform toward a fully funded model based on business-to-business partnerships and sharia-compliant investment instruments as an alternative pension design that is more equitable, sustainable, and consistent with Maqashid Sharia.